2015
DOI: 10.5114/fn.2015.56544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mGluR5 positive and negative allosteric modulators on brain damage evoked by hypoxia-ischemia in neonatal rats

Abstract: A b s t r a c t In the present study, we examined the effects of negative and positive allosteric modulators of metabotropic glutamate receptor 5 (mGluR5), fenobam and ADX47273, respectively, on brain damage induced by hypoxia-ischemia (H-I) in 7-day-old rats. The test drugs were administered intraperitoneally 10 min after H-I. Rectal body temperature was measured for 2.5 h after the insult. The number of apoptotic neurons in the immature rat brain was evaluated after 24 h. The wet weight of both hemispheres w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Moreover, mGluR5 has been shown to protect astrocytes from ischemic damage in the postnatal central nervous system (CNS) white matter (Vanzulli and Butt, 2015). However, other studies have found that antisense oligodeoxynucleotide directed to mGluR5, MPEP or MTEP, showed no neuroprotective effects against post-traumatic neuronal injury (Mukhin et al, 1996) in vitro , OGD damage (Meli et al, 2002), or hypoxia-ischemia injury in neonatal rats (Makarewicz et al, 2015). Moreover, the use of CHPG did not improve the functional and histological outcomes in a rat model of endothelin-1-induced focal ischemia (Riek-Burchardt et al, 2007).…”
Section: Roles Of Mglurs In Cerebral Ischemiamentioning
confidence: 99%
“…Moreover, mGluR5 has been shown to protect astrocytes from ischemic damage in the postnatal central nervous system (CNS) white matter (Vanzulli and Butt, 2015). However, other studies have found that antisense oligodeoxynucleotide directed to mGluR5, MPEP or MTEP, showed no neuroprotective effects against post-traumatic neuronal injury (Mukhin et al, 1996) in vitro , OGD damage (Meli et al, 2002), or hypoxia-ischemia injury in neonatal rats (Makarewicz et al, 2015). Moreover, the use of CHPG did not improve the functional and histological outcomes in a rat model of endothelin-1-induced focal ischemia (Riek-Burchardt et al, 2007).…”
Section: Roles Of Mglurs In Cerebral Ischemiamentioning
confidence: 99%
“…), others play a role in matching oligodendrocytes to the axonal surface (cell adhesion molecule L1, the polysialylated neuronal cell adhesion molecule: PSA-NCAM; Jagged 1). Similarly, neuron survival and proficient functioning strongly depends on oligodendrocytes and compact myelin sheath [ 170 – 173 ]. Keeping the above in mind, both the compounds protecting either neurons or oligodendrocytes, as well as those preserving the myelin structure, might turn out to be effective in preventing white matter damage and subsequent neurodevelopmental disorders.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…The most effective treatment is to regain blood perfusion, which, however, may cause secondary injury on brain tissues [3,4]. Brain ischemia-reperfusion damage is associated with a complicated patho-physiology process, which includes neurodegeneration, apoptosis or necrosis of neurons [5,6]. Neurotransmitter plays a critical role in the occurrence of ischemia cerebrovascular disease [7,8].…”
Section: Introductionmentioning
confidence: 99%